(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: The study aimed to see the effectiveness and role of ivabradine on the quality of life in chronic heart failure suffering patients. This open-label Randomized controlled Trial was conducted to assess the effect of ivabradine plus conventional medical management over conventional medical management on quality-of-life parameters among 100 patients of chronic heart failure from January 2021 to December 2021 in the Department of Pharmacology & Therapeutics in collaboration with the Department of Cardiology & Medicine, Rajshahi Medical College Hospital, Rajshahi. Materials and methods: According to the drug allocation study population was divided into a control group (50 patients) and an experimental group (50 patients). Minnesota Living with Heart Failure questionnaire (MLWHFQ) was used to assess the quality of life, and the resting heart rate was measured by 12-lead electrocardiography. Baseline demographic and clinical characteristics were recorded, and patients were followed up at four weeks and 12 weeks of treatment. Results: The comparison of mean differences of MLWHFQ score at first and second follow-up visits between the two study groups was statistically significant [t (100) = 2.43 p < 0.05 & t (100) = 6.60 p < 0.001 respectively]. According to the MLWHFQ cut-point score, it was also observed that poor baseline quality of life gradually shifted to good quality after four weeks and 12 weeks of treatment, and it was proportionately higher in the experimental group. Relations between the respondents of both study groups and their different qualities of life during the first follow-up visit (x2 = 13.69, df = 2, p < 0.05) and second follow-up visit (x2 = 22.79, df = 2, p < 0.001) were statistically significant.The comparison of the mean (±SD) heart rate between the two study groups was statistically significant (p <0.001) only during the second follow-up visit. Conclusion: This study concluded that adding ivabradine to conventional medical management in treating patients with chronic heart failure improves their symptoms, quality of life, and heart rate and ultimately reduces the morbidity and mortality of such patients. TAJ 2022; 36: No-1: 1-8